2017
DOI: 10.1371/journal.pone.0181929
|View full text |Cite
|
Sign up to set email alerts
|

Contacts in the last 90,000 years over the Strait of Gibraltar evidenced by genetic analysis of wild boar (Sus scrofa)

Abstract: Contacts across the Strait of Gibraltar in the Pleistocene have been studied in different research papers, which have demonstrated that this apparent barrier has been permeable to human and fauna movements in both directions. Our study, based on the genetic analysis of wild boar (Sus scrofa), suggests that there has been contact between Africa and Europe through the Strait of Gibraltar in the Late Pleistocene (at least in the last 90,000 years), as shown by the partial analysis of mitochondrial DNA. Cytochrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…However, Vai et alThe genetic proximity of West Siberian wild boars to European groups can be accounted by the fact that West Siberian population was established as a result of intentional releases of animals presumably from the European part of Russia, Eastern Europe (Belarus), and the Northern Caucasus(Markov & Bolshakov, 1996). As in previous studies (e.g.,Fang & Andersson, 2006;Larson et al, 2005;Soria-Boix, Donat-Torres, & Urios, 2017), this showed a lack of genetically specific groups within continental Western, Central, Eastern Europe, and Northern Africa (Morocco and Tunisia) and the specificity of the Italian population.On the other hand, the MJ network based on the whole mtDNA sequences suggests differences in haplotype composition between Western Europe and Central-Eastern Europe. These results are consistent with those obtained by Zinovieva(2013)using polymorphism of genes associated with quantitative trait loci.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…However, Vai et alThe genetic proximity of West Siberian wild boars to European groups can be accounted by the fact that West Siberian population was established as a result of intentional releases of animals presumably from the European part of Russia, Eastern Europe (Belarus), and the Northern Caucasus(Markov & Bolshakov, 1996). As in previous studies (e.g.,Fang & Andersson, 2006;Larson et al, 2005;Soria-Boix, Donat-Torres, & Urios, 2017), this showed a lack of genetically specific groups within continental Western, Central, Eastern Europe, and Northern Africa (Morocco and Tunisia) and the specificity of the Italian population.On the other hand, the MJ network based on the whole mtDNA sequences suggests differences in haplotype composition between Western Europe and Central-Eastern Europe. These results are consistent with those obtained by Zinovieva(2013)using polymorphism of genes associated with quantitative trait loci.…”
mentioning
confidence: 89%
“…Andersson, 2006;Larson et al, 2005;Soria-Boix, Donat-Torres, & Urios, 2017), this showed a lack of genetically specific groups within continental Western, Central, Eastern Europe, and Northern Africa (Morocco and Tunisia) and the specificity of the Italian population.On the other hand, the MJ network based on the whole mtDNA sequences suggests differences in haplotype composition between Western Europe and Central-Eastern Europe. The division of samples on the MJ network is however in general agreement with clusters E1-A and E-1C described inScandura et al (2011).…”
mentioning
confidence: 91%